Entrepreneurship training course for mentors and pupils:a MOOC experience in HEI and business - Barbas, Maria (2020)
This work is being carried out in the context of the project ‘Starting Up – Accelerators of Entrepreneurship 4 Inclusion’ and it aims, among other things, at the development of an Entrepreneurship Training Course for Mentors and Pupils, following a Massive Open Online Course (MOOC) approach. The target group of this MOOC is pupils with Intellectual and Developmental Difficulties (IDD pupils), as well as their mentors. The MOOC was developed according to the needs of pupils with IDD. In order to create a strong and sustainable course, the following steps were implemented: (a) the identification and creation of tools for mentors who work with this population; (b) the development of interactive and visual contents to increase students’ motivation; (c) the study of the needs of the labour market were the pupils will be workers or entrepreneurs; (d) the development of contents that helps to strengthen labour skills, both for employment and self-employment. The course was developed in an innovative and enhanced way, using various multimedia content (texts, images, audios, and videos) as well as using the best practices of accessibility and usability (e.g., HTML5). The MOOC approach ensures an easy way for pupils to access and use the platform, but also increases the transferability of the contents. The MOOC is organized into two sections. The first section is a course for mentors. It aims to develop mentors’ skills and competencies to teach IDD pupils and give them support in employment and self-employment processes. Some other topics included are the preparation of the mentors to promote the inclusion of people with disabilities in the labour market, and the challenges and opportunities of employability in digital environments. The second section was designed for IDD pupils and is organized in two main topics: (a) the development of pupils’ skills in order for them to create a winner profile, with contents including: how to create an e-portfolio, how to prepare an interview, sharing of good practices, connecting with job platforms etc. and (b) the promotion of a successful life in the labour market, namely through employment, self-employment, and sharing of success cases. To assess the contents of the MOOC, two surveys were implemented. The first was applied to future possible tutors. They were trained professors in the field of education. These professors analyzed the MOOC contents and structure and provided feedback to improve it. The second survey was applied to ten IDD pupils, after testing the platform contents. The feedback of each public was used to improve the MOOC. The MOOC is an open access platform and a free tool to promote the employment and self-employment of IDD pupils. Future tests will be made with real tutors and IDD pupils.